2017
DOI: 10.1186/s12884-017-1565-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations of childhood maltreatment with pre-pregnancy obesity and maternal postpartum mental health: a cross-sectional study

Abstract: BackgroundPre-pregnancy obesity and postpartum mental disorders are prevalent health risks to both the mother and the offspring. The objective of our study was to examine whether a history of childhood maltreatment is associated with pre-pregnancy obesity and postpartum mental health and whether childhood maltreatment and pre-pregnancy BMI independently predict postpartum mental health.MethodsWe obtained self-reported data from 741 postpartum women before 16 weeks after delivery (M = 8.1 weeks, SD = 3.2). Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 63 publications
0
5
0
1
Order By: Relevance
“…Parte de los estudios publicados evaluó los traumas en la infancia con un único constructo (10,32) , sin analizar sus tipos. En este estudio evaluamos los tipos de trauma vividos en la infancia de otra manera, explorado (33) . Sin embargo, diversos estudios publicados con anterioridad en los que se evaluó a mujeres durante el período posparto no indicaron ninguna relación directa entre diferentes tipos de traumas en la infancia y DPP (34) .…”
Section: Discussionunclassified
“…Parte de los estudios publicados evaluó los traumas en la infancia con un único constructo (10,32) , sin analizar sus tipos. En este estudio evaluamos los tipos de trauma vividos en la infancia de otra manera, explorado (33) . Sin embargo, diversos estudios publicados con anterioridad en los que se evaluó a mujeres durante el período posparto no indicaron ninguna relación directa entre diferentes tipos de traumas en la infancia y DPP (34) .…”
Section: Discussionunclassified
“…Parents with a history of violence are also more likely to have multiple socio-economic challenges, including unintended pregnancies ( 39 ), antenatal and postnatal depression ( 40 ), contact with the justice system and low employment ( 41 ) which can also preclude the capacity of parents to nurture and care for children ( 38 ). Our findings support other studies reporting that experience of multi forms of violence is associated with greater adverse impacts ( 9 , 25 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a larger Australian study [87] showed a similar but lower risk for CEA (aOR = 1.4). Nagl et al [88] found that women with severe CEA were nearly 20 times more likely to have PPD. Severe CPA or CSA, slight and moderate CPA, or CEA were lesser risk factors.…”
Section: Postpartum Depression (Ppd)mentioning
confidence: 99%